2021
DOI: 10.1186/s43066-021-00154-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential relation between non-alcoholic fatty liver disease and glycemic and metabolic parameters in subjects without diabetes

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is proved to be related to insulin resistance and type 2 diabetes, and it is also not rare in individuals without diabetes. The present study attempts to identify the metabolic risk factors of NAFLD among those individuals. Results ALT and HbA1c levels were independently associated with NAFLD development in individuals without diabetes. Receiver operating characteristic (ROC) analysis identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Moreover, it deranged insulin inhibition of hepatic glucose production and affected insulin sensitivity in muscle and adipose tissue. 9,45 Consequently, the obtained results revealed that feeding rats with HFD and injection with STZ impaired glucose homeostasis, lipid metabolism, and tissue insulin sensitivity. This was evident via the higher levels of blood glucose (hyperglycemia) and insulin (hyperinsulinemia), and the increased value of HOMA-IR confirming the insulin resistance status in both HFD (obese) and HFD/STZ (diabetic) rats.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, it deranged insulin inhibition of hepatic glucose production and affected insulin sensitivity in muscle and adipose tissue. 9,45 Consequently, the obtained results revealed that feeding rats with HFD and injection with STZ impaired glucose homeostasis, lipid metabolism, and tissue insulin sensitivity. This was evident via the higher levels of blood glucose (hyperglycemia) and insulin (hyperinsulinemia), and the increased value of HOMA-IR confirming the insulin resistance status in both HFD (obese) and HFD/STZ (diabetic) rats.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, it deranged insulin inhibition of hepatic glucose production and affected insulin sensitivity in muscle and adipose tissue. 9 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the importance of glycemic control in reducing the odds of severe NAFLD. Recent studies in several countries have found an association between HbA1c and NAFLD in general or normoglycemic populations ( Tanaka et al, 2019 ; Masroor and Haque, 2021 ; Naguib and Kassab, 2021 ), but most have not evaluated the association within patients with prediabetes or diabetes. One of these previous studies found that the association held after controlling for diabetes status, consistent with our findings ( Masroor and Haque, 2021 ).…”
Section: Discussionmentioning
confidence: 99%